A CRITICAL REVIEW OF NORMATIVE ACCOUNTING THEORY IN THE CONTEXT OF SUSTAINABILITY REPORTING - Sovannah Phengsavang (CV. Fahr Publishing, 2024)
This study critically examines the alignment between normative accounting theory and contemporary sustainability reporting practices, aiming to evaluate whether current reporting frameworks such as the Global Reporting Initiative (GRI) and the International Sustainability Standards Board (ISSB) uphold ethical accountability and stakeholder inclusiveness. Employing a qualitative library research method, this paper synthesizes peer-reviewed literature, institutional reports, and academic frameworks through thematic analysis. The findings reveal a significant conceptual gap between the ethical foundations of normative theory—which emphasize fairness, long-term responsibility, and transparency—and the practice of sustainability reporting, which often prioritizes financial materiality and investor-oriented disclosures. A key novelty of this research lies in its normative critique of modern reporting frameworks, offering a structured theoretical lens to evaluate ethical shortcomings and propose more philosophically grounded reporting practices. Additionally, the study highlights the lack of integration of normative principles within professional accounting education and standard-setting processes. It contributes to global accounting discourse by emphasizing the role of moral reasoning in shaping sustainability standards and by suggesting that a more ethically committed reporting culture is essential for achieving authentic corporate accountability. In conclusion, the study advocates for a paradigm shift in how sustainability reporting is conceptualized and implemented—moving beyond compliance and technical disclosure toward a model rooted in normative ethics and stakeholder justice